The diagnosis and treatment of migraine among medical students in 2010–2011 and 2019 - E. Bacevičiūtė; A. Ekkert; K. Noreikaitė; K. Ryliškienė (Neurologijos seminarai)
Background. Migraine prevalence in Lithuania is 18.8%. The aim of this study was to evaluate the prevalence of migraine, quality of life, professionally confirmed diagnosis rate, and treatment among medical students (aged 18-28 years) in 2010-11 and in 2019. Materials and methods. 478 Vilnius university medicine and odontology students participated in the anonymous survey. 252 students were queried in 2010-11 study (aged 23.0±7.8) and 226 in 2019 (aged 23.0±1.5). Questionnaire consisted of questions, based on headache characteristics, triggers, impact on life, presence of confirmed diagnosis, and treatment. The data was analyzed by SPSS 23.0 software, a p value of <0.05 was considered significant. Results. Based on questionnaire, prevalence of migraine with and without aura remained stable between the periods of 2010-11 (27.8%) and 2019 (27.9%) (p=0.98); women were affected more often (p=0.02). Pain remained moderately intense (p=0.07), but migraine disability worsened over the time (p=0.01). Migraine was professionally diagnosed more often in 2019 (10% vs. 25.4%, p=0.03); increased use of specific acute therapy (5.7% vs. 19%, p=0.03) and prophylaxis (0% vs 9.6%, p=0.003) was observed. Likelihood of diagnosis significantly increased with more intense pain (OR=2.7, p=0.006) and aura (OR=2.7, p=0.037). Presence of confirmed diagnosis was an independent determinant of increased triptans (OR=6.9, p=0.012) and prophylaxis (OR=30.3, p=0.036) use. Conclusions. Comparing the 2010-11 and 2019 periods, migraine prevalence is similar. Pain remains to be valued as moderate, but quality of life has worsened. Prevalence of professionally diagnosed migraine has increased over the time, what was accompanied by an increased use of triptans and prophylaxis, however, migraine still remains underdiagnosed and undertreated.